2014
DOI: 10.5688/ajpe7810180
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Benefits and Challenges of Interprofessional Education Based on a Multidisciplinary Faculty Member Survey

Abstract: Objective: To identify differences among faculty members in various health professional training programs in perceived benefits and challenges of implementing interprofessional education (IPE). Methods: A 19-item survey using a 5-point Likert scale was administered to faculty members across different health disciplines at a west coast, multicollege university with osteopathic medicine, pharmacy, and physician assistant programs. Results: Sixty-two of 103 surveys (60.2%) were included in the study. Faculty memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 28 publications
2
37
0
Order By: Relevance
“…6 Faculty attitudes and knowledge of IPE in other health professional programs have been evaluated previously. [7][8][9] In this study, knowledge refers to IPE implementation and definition. Faculty attitudes are the personal perception of individual institutions, programs, and their colleagues' ability to implement IPE within RT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Faculty attitudes and knowledge of IPE in other health professional programs have been evaluated previously. [7][8][9] In this study, knowledge refers to IPE implementation and definition. Faculty attitudes are the personal perception of individual institutions, programs, and their colleagues' ability to implement IPE within RT.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies among pharmacy, osteopathic medicine, and physician assistant faculty have reported barriers to IPE implementation due to limited access to other health-care disciplines, the lack of adequate clinical training sites, lack of administrative support, insufficient faculty resources, lack of standardized assessment tools, and little flexibility within curriculum requirements. 10,11 Reeves et al 12 call for additional studies in professionspecific IPE interventions, randomized control trials, and qualitative measures involving IPE and practice changes, and cost-benefit analysis to efficiently expand this field. American health-care educational accrediting bodies currently lack a collective mandate for IPE, although an evaluation found that most programs, such as nursing, used some form of interprofessional language in their accrediting standards.…”
Section: Introductionmentioning
confidence: 99%
“…revealed that medical faculty had a significantly lower mean score than that of their nursing counterparts. Lash et al (2014) found that faculty from medicine had lower opinion scores of perceived support for IPE when compared to the scores of colleagues of pharmacy and physician assistant programs. Lower results among medical faculty explain why learning and teaching with nursing and other health faculty members is an important strategy for addressing stereotypes.…”
Section: Challenges Of Interprofessional Health Educationmentioning
confidence: 99%
“…The rise of interest in interprofessional practice and education is shared by health educators in Canada (Bilodeau, Dubois, & Pepin, 2013;D'Amour & Oandasan, 2005;Gilbert, 2005a;Pfaff, Baxter, Jack, & Ploeg, 2013), the United Kingdom (Barr & Low, 2013;Barr, Helme, & D'Avray, 2011;Lewy, 2010;Reeves, Perrier, Golman, Freeth, & Zwarenstein, 2013), the United States of America (Lash et al, 2014), and Norway (Kyrkjebø, Brattebø, & Smith-Strøm, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Successful interprofessional learning can develop students' ability to communicate and work with other professionals, potentially improving the environment for service users and professionals." Medical students tend to be more negative about IPE (Lash et al 2014). However as Harden (2015) states if doctors are to practice effectively within multi-disciplinary teams they need to have an understanding and respect of the roles of other professions.…”
Section: Rationale For Ipementioning
confidence: 99%